PENGARUH PENGUNGKAPAN CSR, KEBIJAKAN DIVIDEN, KEPEMILIKAN INSTITUSIONAL, LEVERAGE, PROFITABILITAS, DAN TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN - Indilla, Faizah Ikramina; Yuliani, Rahma (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
The objective of this study is to investigate the effects of corporate social responsibility (CSR) disclosure, dividend policy, institutional ownership, leverage, profitability, and tax avoidance on firm value. The intention is to comprehend how these elements affect firm value amidst the dynamic market challenges, thereby providing insights to stakeholders. The research population consisted of consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange during 2021-2022, with sample collected through purposive sampling, resulting in 21 companies and yielding 42 sample units. The analytical methodology employed multiple linear regression supported by SPSS 29. The research findings highlight that dividend policy and profitability have an effect on firm value, consistent with signalling theory. However, CSR disclosure, institutional ownership, leverage, and tax avoidance do not affect firm value